Atividade docente no capitalismo: uma análise da produção acadêmica a partir da categoria trabalho - Oliveira, Maíra dos Santos (2013)
The research present have study object ´´the nature of the teaching activity performed in capitalism`` and has as its general objective: "to analyze the teaching activity carried on in the capitalist mode of production, from the work category, in order to verify how it is being discussed the nature of this activity in academic productions". This is a literature whose sources are secondary. Appropriates historical and dialectical materialism as a method, which involves asserting that reality is the starting point of the whole analysis. The chapters presented deal with the development of human sociality process whose central category is the work, the resulting changes to the capitalist mode of production, addressing two central categories to understand it today: productive and unproductive labor. Approach the nature of teaching activity from these categories and dialogue with the academic productions that deal with this theme and are available at the Bank of CAPES thesis. The research allows to characterize the teaching activity as a situated action in the list of secondary teleological positions; argue that although it is employed, the teacher is not productive worker, since it does not produce nor asset value, and assert that there is only one nature of teaching activity determinations suffering differentiated depending on the sphere to which it is subjected.